2019
DOI: 10.1037/xge0000553
|View full text |Cite
|
Sign up to set email alerts
|

Visual illusions help reveal the primitives of number perception.

Abstract: Grouping effects in numerosity perception under prolonged viewing conditions. PLoS ONE, 14(2), e0207502.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 54 publications
5
35
1
Order By: Relevance
“…That is, congruity effects may reflect a perceptual interaction between numerical and non-numerical dimensions, wherein the irrelevant dimension influences perception of the relevant dimension, making it difficult to attend to, and judge only, the relevant dimension. Importantly, such effects may also reflect discriminability of the dimensions (with more discriminable dimensions exerting greater influence over less discriminable dimensions), and there may also be entirely different magnitude interactions that arise via non-perceptual mechanisms (e.g., response stage; Picon, Dramkin, & Odic, 2019) such as when judgments of Arabic numerals are affected by the physical sizes of those numerals (e.g., Henik & Tzelgov, 1982). Future work will be needed to directly examine what mechanisms (perceptual vs. non perceptual) underlie specific effects, such as congruency effects on tasks of explicit magnitude comparison, given that the present work provides evidence for perceptual mechanisms underlying some magnitude interactions, not that there are only perceptual mechanisms underlying all magnitude interactions.…”
Section: Discussionmentioning
confidence: 99%
“…That is, congruity effects may reflect a perceptual interaction between numerical and non-numerical dimensions, wherein the irrelevant dimension influences perception of the relevant dimension, making it difficult to attend to, and judge only, the relevant dimension. Importantly, such effects may also reflect discriminability of the dimensions (with more discriminable dimensions exerting greater influence over less discriminable dimensions), and there may also be entirely different magnitude interactions that arise via non-perceptual mechanisms (e.g., response stage; Picon, Dramkin, & Odic, 2019) such as when judgments of Arabic numerals are affected by the physical sizes of those numerals (e.g., Henik & Tzelgov, 1982). Future work will be needed to directly examine what mechanisms (perceptual vs. non perceptual) underlie specific effects, such as congruency effects on tasks of explicit magnitude comparison, given that the present work provides evidence for perceptual mechanisms underlying some magnitude interactions, not that there are only perceptual mechanisms underlying all magnitude interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This theory ts well with the characteristics of lateral inhibition of neurons in early visual pathways and the known properties of activation as measured with fMRI (Schwarzkopf, Song, & Rees, 2011). Rose and Bressan (2002) researched the Ebbinghaus illusion (see Fig 1B), which is closely related to the Delboeuf illusion (Girgus, Coren, & Agdern, 1972;Mruczek et al, 2017;Picon, Dramkin, & Odic, 2019;Roberts et al, 2005), by same-shape illusions (i.e., with an identically shaped test and inducer) and different-shape illusions (i.e., the test gure was a circle and the inducers were circles, hexagons, triangles, or angular shapes). The results showed that inducer shape had a signi cant effect; same-shape illusions were signi cantly larger than different-shape illusions with circles or triangles as the test stimuli.…”
Section: Introductionmentioning
confidence: 86%
“…Visual illusions could be the ideal tool to dissociate the subjective perception of (discrete) numerosity from continuous features because they help to reveal the relationship between physical stimulation (e.g., at the retinal level) and the subjective perception of the visual input. Therefore, they can be used to selectively manipulate a visual feature without compromising other physical visual features in the image (e.g., Picon et al, 2019 ). For instance, the connectedness illusion has been used to manipulate the level of perceived segmentation of the items in a set, keeping constant the low-level features across connectedness levels (Adriano, Girelli, et al, 2021 ; Adriano, Rinaldi, et al, 2021 ; Franconeri et al, 2009 ; Kirjakovski & Matsumoto, 2016 ).…”
mentioning
confidence: 99%
“…Size illusions are perceptual phenomena in which the physical size of a stimulus is altered by contextual cues. For instance, Picon et al ( 2019 ) contingently manipulated numerosity and perceived size, embedding numerical arrays in the classic Ebbinghaus illusion context. Results showed that participants significantly overestimated the number of dots presented in a perceived larger convex hull and underestimated the number of dots presented in the perceived smaller convex hull.…”
mentioning
confidence: 99%